Photocatalytic Bactericidal Efficiency of Ag Doped TiO2/Fe3O4 on Fish Pathogens under Visible Light - Ekkachai Kanchanatip; Nurak Grisdanurak; Naichia Yeh; Ta Chih Cheng (International Journal of Photoenergy)
This research evaluates photocatalytic bactericidal efficiencies of Ag-TiO2/Fe3O4 in visible light using target pollutants that include Aeromonas hydrophila, Edwardsiella tarda, and Photobacterium damselae subsp. piscicida. The investigation started with Ag-TiO2/Fe3O4 synthesis and calcination followed by a series of product tests that include the examination of crystallite phase, light absorption, element composition morphology, and magnetic properties. The results of the experiment indicate that Ag and Fe3O4 significantly enhanced the light absorption capacity of TiO2 in the entire visible light range. The Ag-TiO2/Fe3O4 prepared in this study displays significantly enhanced visible light absorption and narrowed band gap energy. The magnetic property of Ag-TiO2/Fe3O4 made it easy for retrieval using a permanent magnet bar. The photocatalytic activity of Ag-TiO2/Fe3O4 remains above 85% after three application cycles, which indicates high and favorable efficiency in bactericidal evaluation. The experiments have proved that the Ag-TiO2/Fe3O4 magnetic photocatalyst is a promising photocatalyst for antibacterial application under visible light.